GOAT DISEASE DIAGNOSIS WITH THE CERTAINTY FACTOR METHOD - Beriyanto; Purwidayanta, Sanyata (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
System expert diagnosis disease goat this web- based designed For help breeders in identify goat disease​ in a way more fast and accurate.Using Certainty Factor method , system This can determine level certainty of diagnosis based on symptoms inputted by the user and provide diagnostic results and level certainty in form percentage . Research This covers design in implementation system , start from collection of disease and symptom data goat until testing system use Black Box method . Testing show that system functioning in accordance with specifications set and capable​ give results accurate diagnosis . Manual and system test results to a number of test cases show consistent Certainty Factor value , with accuracy system by 96.67% of the system This prove its potential as reliable solution​ For increase efficiency and effectiveness diagnosis disease goat , giving benefit significant for breeders in maintaining livestock health they .